2012
DOI: 10.1002/cssc.201100633
|View full text |Cite
|
Sign up to set email alerts
|

Development of New Hydrogenations of Imines and Benign Reductive Hydroaminations: Zinc Triflate as a Catalyst

Abstract: The hydrogenation of imines to amines in the presence of catalytic amounts of zinc triflate has been demonstrated for the first time. In addition, an efficient procedure for the reductive hydroamination of alkynes to amines is presented using zinc triflate as a catalyst precursor. In both protocols a variety of different functional groups are tolerated, and the reactions proceed smoothly in high yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 68 publications
(38 citation statements)
references
References 142 publications
1
37
0
Order By: Relevance
“…While testing different Lewis acids for the hydrogenation of para-methoxy-N-(1-phenylethylidene)aniline 1 a (p-me thoxyphenyl = PMP) to give the corresponding amine 2 a, to our surprise ZnA C H T U N G T R E N N U N G (OTf) 2 was discovered as a suitable catalyst. [12] In Table 1, selected reactions from the previous optimization studies are shown. For example, using 5 mol % of simple ZnA C H T U N G T R E N N U N G (OTf) 2 without any ligand at 100 8C afforded 2 a in 72 % yield ( Table 1, entry 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While testing different Lewis acids for the hydrogenation of para-methoxy-N-(1-phenylethylidene)aniline 1 a (p-me thoxyphenyl = PMP) to give the corresponding amine 2 a, to our surprise ZnA C H T U N G T R E N N U N G (OTf) 2 was discovered as a suitable catalyst. [12] In Table 1, selected reactions from the previous optimization studies are shown. For example, using 5 mol % of simple ZnA C H T U N G T R E N N U N G (OTf) 2 without any ligand at 100 8C afforded 2 a in 72 % yield ( Table 1, entry 1).…”
Section: Resultsmentioning
confidence: 99%
“…During our investigations on ironcatalyzed enantioselective imine hydrogenations, [11] we discovered that similar reductions proceed in the presence of catalytic amounts of simple zinc(II) triflate. [12] Most recently, we were able to perform atom-efficient reductive hydroaminations of alkynes with this unique catalyst. However, to the best of our knowledge no asymmetric hydrogenations using zinc catalysts are known.…”
Section: Introductionmentioning
confidence: 99%
“…The conversion of imides to amines is promoted by zinc triflate in toluene and in the same publication the reductive hydroamination of alkynes is presented (Werkmeister et al 2012). These reactions demand high pressure and temperature, but the catalysts are not as expensive as some others and they are simple, selective and efficient.…”
Section: Chaptermentioning
confidence: 99%
“…Herein, the results of the experiments carried out to determine the retention rate of the catalyst in different ternary solvent mixtures are presented. Different catalysts were previously tested for the continuous esterification of ethanol and acetic acid, for the hydrogenation of imides , carbon dioxide as well as the hydrogenation of ethyl acetate. In an approach to create a biphasic system, cyclohexane was added to the reaction to allow a liquid‐liquid extraction previous to the OSN process.…”
Section: Introductionmentioning
confidence: 99%